2022
DOI: 10.3390/polym14102009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Thermal Parameters of Geopolymers Modified with Iron Powder

Abstract: The paper presents the results of research concerning the influence of a metallic micromaterial on the thermal conductivity λ, specific heat Cp, and thermal diffusivity a of modified geopolymers. Iron oxide in the form of powder with an average granulation of 10 μm was used as the geopolymer-modifying material. The research concerned geopolymer composite samples with metakaolin (activated with potassium silicate) and the addition of iron in amounts ranging from 0.5% to 2.5% in relation to the weight of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…For these reasons, Fe is considered incompatible with GPs at elevated temperatures (above 800 °C). 49,51,198 GPs with higher iron oxide contents also show lower acid resistance, even when compared to OPCs. 199 With regards to mechanical properties, some recent studies have reported higher compressive, flexural, and tensile strengths of iron-bearing GPs, which has been ascribed to the filler effects of iron oxides and the combined action of polysialates, iron-silicates, and ferro-sialates (Fe(−Al)−S− H).…”
Section: Si To M and Al To M Ratiosmentioning
confidence: 99%
See 4 more Smart Citations
“…For these reasons, Fe is considered incompatible with GPs at elevated temperatures (above 800 °C). 49,51,198 GPs with higher iron oxide contents also show lower acid resistance, even when compared to OPCs. 199 With regards to mechanical properties, some recent studies have reported higher compressive, flexural, and tensile strengths of iron-bearing GPs, which has been ascribed to the filler effects of iron oxides and the combined action of polysialates, iron-silicates, and ferro-sialates (Fe(−Al)−S− H).…”
Section: Si To M and Al To M Ratiosmentioning
confidence: 99%
“…Only limited research exists regarding the effect of Si/Fe ratios on the properties of GPs. ,, In general, high concentrations of ferric oxide, apart from its impacts on the color of GPs, can give higher specific gravity, enhanced thermal conductivity, and increased thermal expansion of the setting material while also impacting the morphology of GPs after curing at elevated temperatures. For these reasons, Fe is considered incompatible with GPs at elevated temperatures (above 800 °C). ,, GPs with higher iron oxide contents also show lower acid resistance, even when compared to OPCs . With regards to mechanical properties, some recent studies have reported higher compressive, flexural, and tensile strengths of iron-bearing GPs, which has been ascribed to the filler effects of iron oxides and the combined action of polysialates, iron-silicates, and ferro-sialates (Fe­(−Al)–S–H). ,, Other studies, however, have shown that iron can negatively impact GP properties through the rapid precipitation of Fe species due to the higher atomic size of Fe compared to Si or Al, causing more rapid consumption of OH – , which in turn results in deceleration of the dissolution of the remaining precursor and inhibition of the geopolymerization and thus reduced strength of the system. ,, However, as shown by Davidovits, these negative impacts of elevated Fe contents on GP properties may be suppressed, as they achieved improved mechanical durability of GPs even with extremely high quantities of iron.…”
Section: Factors Affecting the Properties Of Gpsmentioning
confidence: 99%
See 3 more Smart Citations